The Pains and Gains of COVID-19 – Challenges to Child First Justice in the Pandemic. (April 2023) - Hampson, Kathy; Case, Stephen; Little, Ross
The global COVID-19 pandemic has particularly affected justice-involved children. Youth justice policy changes and innovations have assisted communication and engagement with these vulnerable children during unprecedented times, while attempting to limit risks of contagion and criminalisation – all central tenets of the 'Child First' guiding principle for the Youth Justice System of England and Wales. While some changes have enhanced the experiences of some justice-involved children (gains), others have disproportionately disadvantaged justice-involved children in court, community and custody contexts (pains), increasing criminalisation, disengagement and anxiety. These pains of COVID-19 have effectively eroded the rights of this already-vulnerable group of children.